2014
DOI: 10.1007/s00586-014-3356-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal surgical care for adolescent idiopathic scoliosis: an international consensus

Abstract: Purpose The surgical management of adolescent idiopathic scoliosis (AIS) has seen many developments in the last two decades. Little high-level evidence is available to support these changes and guide treatment. This study aimed to identify optimal operative care for adolescents with AIS curves between 40°and 90°Cobb angle. Methods From July 2012 to April 2013, the AOSpine Knowledge Forum Deformity performed a modified Delphi survey where current expert opinion from 48 experienced deformity surgeons, representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 60 publications
8
59
0
5
Order By: Relevance
“…12 Routine usage of the postoperative CT scan is currently not recommended given high radiation exposure to the patients, especially in pediatric population. 13 For these reasons we choose the EOS imaging system (EOS imaging SA, Paris, France), 14 which simultaneously produces high-quality biplanar anteroposterior and lateral x-ray images of the whole body in a standing position, with approximately one tenth of the conventional radiography. 15 As these 2D images are automatically calibrated, by matching their anatomic landmarks on a working station, it also provides a 3D model of the whole spine.…”
mentioning
confidence: 99%
“…12 Routine usage of the postoperative CT scan is currently not recommended given high radiation exposure to the patients, especially in pediatric population. 13 For these reasons we choose the EOS imaging system (EOS imaging SA, Paris, France), 14 which simultaneously produces high-quality biplanar anteroposterior and lateral x-ray images of the whole body in a standing position, with approximately one tenth of the conventional radiography. 15 As these 2D images are automatically calibrated, by matching their anatomic landmarks on a working station, it also provides a 3D model of the whole spine.…”
mentioning
confidence: 99%
“…26,32 Furthermore, an international consensus suggested that an implant density less than 80% was optimal (73% vs 27%) for moderate curves with a Cobb angle of 40°-70°. 5 As to sagittal correction, pooled data on thoracic kyphosis were available in 8 studies, involving a total of 475 patients, and no significant differences were found (p = 0.26, I 2 = 79%). The same conclusion was recorded in 2 additional studies (p = 0.15 and p = 0.37).…”
Section: Discussionmentioning
confidence: 99%
“…Während Thorakalskoliosen häufig mit einer Abflachung der thorakalen Kyphose einhergehen, findet sich bei den Thorakolumbalskoliosen häufig eine Rotationskyphose im thorakolumbalen Übergang. Anzumerken ist, dass die konkavseitigen Pedikel so klein waren, dass diese überwiegend uninstrumentiert bleiben mussten [12].…”
Section: Klassifikationunclassified